Problems and Alternative Solutions for the Implementation of Islamic Education Learning during the Pandemic: A Literature Review - I'anatut Thoifah; Saeful Biantoro (Universitas Muhammadiyah Malang, 2021)
This study aims to analyze the problems in the implementation of PAI (Islamic Education) learning, based on the results of preliminary research that the highest percentage of problems in the implementation of PAI learning is 44.4% internet network disturbances. This study uses a qualitative approach to the type of literature review by collecting information and data from various literature (scientific articles) through the google scholar journal search database, researchers enter the boolean operators